1999
DOI: 10.1021/ie990034j
|View full text |Cite
|
Sign up to set email alerts
|

Model for Random Hydrolysis and End Degradation of Linear Polysaccharides:  Application to the Thermal Treatment of Mannan in Solution

Abstract: The kinetics for homogeneous hydrolysis of mannan is studied in a batch reactor at temperatures from 160 to 220°C. A formate buffer ensures a pH of 3.8-4.0, measured at 25°C. Samples are analyzed for oligosaccharides up to a degree of polymerization of 6 and also for the total amount of mannose after acid hydrolysis. A mathematical model with two reactions (1, random hydrolysis of the glucosidic bonds; 2, degradation of the reducing end of the molecule) describes accurately the time course of oligosaccharides.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 28 publications
3
19
0
Order By: Relevance
“…Even though mannose and glucose concentrations increased with a higher severity, the xylose, arabinose and galactose concentrations in the hydrolysates decreased during the most severe conditions, indicating the partial degradation of these sugars in the liquid fraction. This is in accordance with studies that reported a lower activation energy for the hydrolysis of xylan (101 kJ/mol) than for mannan (113 kJ/mol) and cellobiose (110 kJ/mol) hydrolysis (Canettieri et al, 2007; Mosier et al, 2002; Nattorp et al, 1999). It is well known that the combination of high temperature, acidic pH, and prolonged reaction time may contribute to the formation of undesired compounds derived from sugar dehydration, such as furfural and hydroxymethylfurfural, as well as the degradation of phenolic structures (Ferreira-Leitão et al, 2010; Oral et al, 2014).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Even though mannose and glucose concentrations increased with a higher severity, the xylose, arabinose and galactose concentrations in the hydrolysates decreased during the most severe conditions, indicating the partial degradation of these sugars in the liquid fraction. This is in accordance with studies that reported a lower activation energy for the hydrolysis of xylan (101 kJ/mol) than for mannan (113 kJ/mol) and cellobiose (110 kJ/mol) hydrolysis (Canettieri et al, 2007; Mosier et al, 2002; Nattorp et al, 1999). It is well known that the combination of high temperature, acidic pH, and prolonged reaction time may contribute to the formation of undesired compounds derived from sugar dehydration, such as furfural and hydroxymethylfurfural, as well as the degradation of phenolic structures (Ferreira-Leitão et al, 2010; Oral et al, 2014).…”
Section: Resultssupporting
confidence: 92%
“…Reducing sugars when in solution exist as a mix of cyclic structures, which are more resistant to degradation, and as an open chain, which is the more reactive acyclic carbonyl form (Angyal, 1984). In polysaccharides, the sugar at the chain end or ramified end will exist in ring and open chain structures, being more susceptible to degradation (Nattorp et al, 1999). Additionally, it has been shown that at room temperature, glucose and mannose present a lower carbonyl percentage than galactose, xylose, and arabinose (Hayward and Angyal, 1977).…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that saccharides in the open chain form are more readily decomposed when compared to those in the cyclic form under hydrothermal conditions. 43,44 In the present study, since the mannose units remained more stable in the polymerized form than the galactose units because of the slower production of mannose than galactose, mannose decomposition was consequently delayed as compared to galactose.…”
Section: Resultsmentioning
confidence: 62%
“…If the heating was conducted at a higher temperature (such as 85 or 90 • C), the degradation of garlic's polysaccharides was faster in initial stage than in the later stage with a nonlinear relationship between the reciprocal of MW and t (which occurs in systematic processes and mainly in central chains scissions) (Blecker, Fougnies, Van Herck, Chevalier, & Paquot, 2002;Emsley & Heywood, 1995). It was speculated that hydrolysis and depolymerization might begin with the protonation of glycosidic oxygen, before polysaccharides underwent further degradation induced by cyclic carbocation (which resulted from the breakage of glycosidic bonds) (Nattorp, Graf, Spühler, & Renken, 1999).…”
Section: Carbohydratesmentioning
confidence: 99%